1979
DOI: 10.1126/science.569901
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Model for Stretch-Induced Hypertrophy of Skeletal Muscle

Abstract: Mechanical stretch of embryonic chicken skeletal myotubes developed in vitro leads to many of the biochemical changes seen in skeletal muscle hypertrophy. These include increased amino acid accumulation, increased incorporation of amino acids into general cellular proteins and myosin heavy chains, and increased accumulation of total protein and myosin heavy chains. This model system should aid in understanding how the growth rate of skeletal muscle is regulated by its activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
101
0
3

Year Published

1990
1990
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(108 citation statements)
references
References 25 publications
4
101
0
3
Order By: Relevance
“…Earlier reports have shown that mechanical tension alone can regulate cell growth and metabolism and the intracellular signaling proteins may link changes in the tension to this cellular adaptation (46). Recently it has been shown that mechanical stress stimulates the signaling pathways of ERKs, JNKs, and p38 MAP kinases in a variety of cell lines including skeletal muscle cells (8,9,22,23,29).…”
Section: Figmentioning
confidence: 99%
“…Earlier reports have shown that mechanical tension alone can regulate cell growth and metabolism and the intracellular signaling proteins may link changes in the tension to this cellular adaptation (46). Recently it has been shown that mechanical stress stimulates the signaling pathways of ERKs, JNKs, and p38 MAP kinases in a variety of cell lines including skeletal muscle cells (8,9,22,23,29).…”
Section: Figmentioning
confidence: 99%
“…In 1975, Goldberg et al (39) proposed that increased tension development, either passive or active, was the critical event in initiating compensatory growth in mammals. Consistent with the role that mechanical tension plays in regulating skeletal muscle mass in vivo, stretch models have been used to demonstrate that mechanical tension also regulates protein synthesis in vitro (97)(98)(99). Using a cell culture model, Vandenburgh and Kaufman (97,98) demonstrated that intermittent stretch produces a large increase in protein synthesis and a smaller decrease in protein degradation in avian myotubes.…”
mentioning
confidence: 99%
“…Consistent with the role that mechanical tension plays in regulating skeletal muscle mass in vivo, stretch models have been used to demonstrate that mechanical tension also regulates protein synthesis in vitro (97)(98)(99). Using a cell culture model, Vandenburgh and Kaufman (97,98) demonstrated that intermittent stretch produces a large increase in protein synthesis and a smaller decrease in protein degradation in avian myotubes. These data suggest that in cell culture, like models in vivo, the hypertrophic response to increased mechanical tension is due, in part, to an increased rate of protein synthesis.…”
mentioning
confidence: 99%
“…Cells in areas of airspace remodeling likely are subjected to significant alterations in physical and mechanical stress that might play an inductive role. Work on striated muscle has established a dependency of differentiation-specific proteins on generation of tension [Vandenburgh and Kaufman, 1979;Crisona and Strohman, 1983;Riley et al, 19901 and mechanical forces also may regulate matrix production. Recent studies by Kapanci et al [1990] underscore the potential importance of mechanical forces in lung remodeling in that post-capillary hypertension appears to induce SMaA expression in cells of the alveolar wall, perhaps in the cellular actin-containing contractile interstitial cell.…”
Section: The Origin Of Lung Myofibroblastsmentioning
confidence: 99%